Survey on Remote Handling Logistics for Super-FRS. (11th October 2013) - Amjad, Faraz; Weick, Helmut; Mattila, Jouni; Orona, Luis; Kozlova, Ekaterina; Winkler, Martin; Behr, Karl-Heinz; Karagiannis, Christos
Remote Handling (RH) systems are now frequently used to conduct inspections and maintenance in hazardous environments. New particle accelerator facilities present unique logistic challenges due to high radiation levels, a hazardous environment and heavy loads. The Facility for Antiproton and Ion Research (FAIR) will deliver a beam of all ions up to uranium with intensities up to 1012 238 U ions/s, which will cause high levels of radiation during operation so human access is limited. This paper contains a survey on RH logistics for existing High Intensity Beam (HIB) facilities to determine state of the art RH practices and to draw a conclusion based on the analysis. The second part of this paper presents a detailed study of beam losses, the radiation environment, RH logistic challenges and some proposed solutions for Super-FRS. This paper will also suggest a Systems Engineering (SE) approach for developing Super-FRS RH logistics.